2012
DOI: 10.1091/mbc.e11-06-0575
|View full text |Cite
|
Sign up to set email alerts
|

A potentially common peptide target in secreted heat shock protein-90α for hypoxia-inducible factor-1α–positive tumors

Abstract: ETOC: Deregulated/overexpressed HIF-1α is found in many solid tumors, and directly sabotaging it is challenging therapeutically. HIF-1α uses secreted Hsp90α, which uses a key epitope, F-5, for invasion and tumor formation. Drugs that target F-5 may be more effective and less toxic for treatment of HIF-1α–positive tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 50 publications
4
83
0
Order By: Relevance
“…MMP2 is involved in the breakdown of extracellular matrix in normal physiological processes, and altered MMP2 expression contributes to human disease, including cancer development and progression. Another study showed a potentially common peptide target in secreted Hsp90a for hypoxia-inducible factor-1a-positive cancers (14). The authors localized the tumor-promoting effect of Hsp90a to a 115-amino acid region of secreted Hsp90a protein, maintenance of which was sufficient to bypass the blockade of HIF1a depletion and resumed tumor invasion, suggesting that drugs that target these amino acid region could be more effective and less toxic in the treatment of HIF1a-positive cancers (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP2 is involved in the breakdown of extracellular matrix in normal physiological processes, and altered MMP2 expression contributes to human disease, including cancer development and progression. Another study showed a potentially common peptide target in secreted Hsp90a for hypoxia-inducible factor-1a-positive cancers (14). The authors localized the tumor-promoting effect of Hsp90a to a 115-amino acid region of secreted Hsp90a protein, maintenance of which was sufficient to bypass the blockade of HIF1a depletion and resumed tumor invasion, suggesting that drugs that target these amino acid region could be more effective and less toxic in the treatment of HIF1a-positive cancers (14).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed a potentially common peptide target in secreted Hsp90a for hypoxia-inducible factor-1a-positive cancers (14). The authors localized the tumor-promoting effect of Hsp90a to a 115-amino acid region of secreted Hsp90a protein, maintenance of which was sufficient to bypass the blockade of HIF1a depletion and resumed tumor invasion, suggesting that drugs that target these amino acid region could be more effective and less toxic in the treatment of HIF1a-positive cancers (14). Thus, altered expression of Hsp90a protein could serve as a biomarker for different human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of lentiviral systems for downregulation and overexpression of genes are as previously described (Li et al, 2007;Cheng et al, 2008;Sahu et al, 2012). The shRNA sequences for human Hsp90a was 59-GGAAAGAGCTGCATATTAA-39 (sense) and for human Hsp90b was 59-GCATCTATCGCATGATCAA-39 (sense).…”
Section: Chemotaxis Assaymentioning
confidence: 99%
“…The protocols for using lentiviral systems for gene downregulation and gene upregulation, including virus packaging, isolation, infection, and analyses, were as previously described (33,37,42). The pRRLsinh-CMV system was used to overexpress exogenous genes such as the wt and mutant PRAS40 cDNAs.…”
Section: Methodsmentioning
confidence: 99%
“…We used CRISPR/cas9 to NTA analysis of 100,000 ϫ g pellet fractions from conditioned medium of 3 ϫ 10 6 cells, as indicated. **, P Ͻ 0.05; ***, P Ͻ 0.005. knock out both alleles of the Hsp90␣ gene in MDA-MB-231 breast cancer cells (41) that have been shown to constitutively secrete exosomes and Hsp90␣ (42,43). As shown in Fig.…”
mentioning
confidence: 99%